(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
AIDS goes severe health apprehension in Pakistan nowadays and many individuals were infected due to the lack of awareness. HIV concordant couples encountered impediments in way of HIV disclosure such as fear of stigma, loss of ‘Face’, disregard, discrimination, loss of job, and the demise of social circle. Individuals come across condemnation and social disapproval as a result of the HIV diagnosis. The present research employed the phenomenological design of qualitative research and purposive sampling was used to choose the 12 HIV concordant couples from PIMS HIV treatment center, Islamabad. We have taken 24 in depth interviews by using semi structured interview guide. The transcripts were analyzed by qualitative thematic analysis. The researcher has used four themes such as, biographical disruption, embodiment of stigma, ethical dilemma and loss of job. HIV individuals have a fear to disclose their HIV status because of social, financial and biographical disruption. There is a need for the time to emphasize the health of HIV concordant couples and provide the social vaccine for their stable social standing and achieve normalcy in life. The study suggests educating the public through seminars or social media to reduce stigma against people with HIV/AIDS. Providing counseling and social support is essential for HIV/AIDS couples.